Mechanical properties and morphologies of polypropylene composites synergistically reinforced-toughened by styrene–butadiene rubber and graphene oxide nanosheets. (March 2020) - Wang, Zhengjun; Guo, Yi; Yan, Lei; Bian, Jun; Liu, Hongcai; Huang, Huan; Lin, Hailan; Sude, Ma; Lijun, Wang; Gu, Zhijie
Chemically reduced graphene (C- r GO) nanosheets were first prepared from graphene oxide (GO), and then the polypropylene (PP) composites synergistically reinforced–toughened by styrene–butadiene rubber (SBR), and C- r GO nanosheets were fabricated via melt blending. The mechanical properties of PP can be considerably improved by synergistically filling with C- r GO nanosheets and SBR, especially for the notched Izod impact strength (IS). The results from the X-ray diffraction, polarizing optical micrographs, scanning electron microscope, differential scanning calorimetric, dynamic mechanical analysis, and thermogravimetric analysis measurements reveal that: (1) the β -phase crystal structure of the PP is formed when the C- r GO and SBR are synergistically filled with PP and its formation plays a role for the enhancement of the impact strength for PP/SBR/C- r GO composites; (2) the dispersion of the C- r GO and SBR in the PP/SBR/C- r GO composites is homogeneous, indicating that synergistic incorporating method decreases the aggregation of nanosheets and thus increases the sites for dissipation of shock for impact energy in the PP/SBR/C- r GO composites; and (3) the thermal analysis shows high thermal stability for the PP/SBR/C- r GO composites.